2009
DOI: 10.1111/j.1532-5415.2008.02123.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Diastolic Ambulatory Blood Pressure Is Associated with Greater All‐Cause Mortality in Older Patients with Hypertension

Abstract: In older patients with hypertension, low DBP and high PP, particularly when measured using ambulatory BP monitoring, are associated with greater risk of death. The achievement of an SBP treatment goal should not be obtained at the expense of an excessive DBP reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 25 publications
(31 reference statements)
2
33
0
Order By: Relevance
“…The phenomenon of increased mortality with intensive reduction of DBP in individuals aged ⩾ 65 years has been demonstrated in various studies, 13,30 and a pathophysiological basis for the Figure 3. Association of SBP and all-cause mortality, stratified by walking speed.…”
Section: Discussionmentioning
confidence: 96%
“…The phenomenon of increased mortality with intensive reduction of DBP in individuals aged ⩾ 65 years has been demonstrated in various studies, 13,30 and a pathophysiological basis for the Figure 3. Association of SBP and all-cause mortality, stratified by walking speed.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, advanced age, female sex, and diabetes mellitus, but not treatment status, were associated with low DBP. Similarly, Ungar et al 17 showed that low ambulatory DBP was associated with greater all-cause mortality in older patients with ISH after adjusting for antihypertensive treatment and other covariates. The Framingham Heart Study 14 showed that a DBP of <70 mm Hg versus DBP 70 to 89 mm Hg in the absence of antihypertensive therapy could add a risk equivalent of ≈20 mm Hg of increase in SBP-in other words, a potential risk-equivalent shift from prehypertension to stage 1 systolic hypertension or from stage 1 to stage 2 systolic hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…14 Some, but not all, studies including elderly persons have shown associations of lower DBP with higher risk for cardiovascular events and death. 7,1517 Whether measures of functional status can identify the elders in whom low DBP is associated with increased risk cardiovascular events and death has not been well established.…”
Section: Introductionmentioning
confidence: 99%